AB0162 IMPLEMENTATION OF HYDROXYCHLOROQUINE AT THE PRE-CONCEPTIONAL STAGE IN THE TREATMENT OF ANTIPHOSPOLIPID SYNDROME ASSOCIATED WITH SYSTEMIC LUPUS ERYTHEMATOSUS. (June 2019) - Bublikov, Dmitrii; Nikolaeva, Marina
Abstract : Background: The problem of correcting the antiphospholipid syndrome (APS) at the planning stage of pregnancy of patients with systemic lupus erythematosus (SLE) is an important task of rheumatology. Objectives: To study the effect of hydroxychloroquine (HC) on the level of antiphospholipid antibodies titer in women with SLE of low degree of activity at the planning stage of pregnancy. Methods: The study included 7 women aged from 18 to 44 years with a definite diagnosis of low-level SLE (1–5 points according to the SLEDAI2K scale) and confirmed APS. All patients were characterized by a history of three or more reproductive losses in the gestational age of 10 weeks or more. According to standard laboratory tests, the level of antibodies to cardiolipin ( IgM/IgG ) and/or to β2-glycoprotein I ( IgM/IgG ) (β2GPI) in a titer above 99 percentile was determined twice in a 12-week interval. Before inclusion in the study, patients received methylprednisolone and acetylsalicylic acid in the recommended dosages. Other drugs potentially affecting the activity of SLE or hemostasis indicators of the patient during the observation period were not administered. At the time of inclusion, patients were prescribed with hydroxychloroquine (HC) in a dose of 400 mg per day orally, in addition to the therapy received earlier. The titer of antibodies to cardiolipin ( IgM/IgG ) and antibodies to β2GPI ( IgM/IgG ) was determined three times: initially, after 3 and 6 months from the start of therapy. Statistical data processing was performed using the MS Excel 2010 statistical software package and MedCalc Version 17.9.7. Data of laboratory parameters are presented in the form of median (Me) and 95% confidence interval (95% CI). Comparison of dependent samples was performed using non-parametric methods (Wilcoxon Signed Ranks Test). The statistical significance of the hypotheses was accepted at a level of p <0.05. Results: The initial SLEDAI2K index constituted 4.0±1.0 points. The median of the level of antibodies to cardiolipin is defined as 69.2 [95% CI 57.4 - 80.0] U/ml., antibodies to β2GPI - 69.24 [95% CI 49.7 - 87.5] U/ml. After 3 and 6 months from the start of HC administration, the SLEDAI2K index did not statistically significantly change (p=0.09). 3 months later, a statistically significant decrease in the level of antibodies to cardiolipin ( IgM/IgG ) by 30.4% was determined relative to the initial one [Me 21.43 (95% CI 20.2-46.1), p = 0.001]. By the 6th month of therapy, a reduced level of antibodies to cardiolipin remained unchanged; there was no statistically significant difference between the rates after 3 and 6 months of HC therapy. The level of antibodies to β2GPI ( IgM/IgG ) after three months from the start of therapy remained at the level of the indicator before inclusion in the study. A statistically significant decrease in the level of antibodies to β2GPI by 28.5% compared to the initial one was determined 6 months after the start of HC administration [Me 19.17 (95% CI 10.8-27.4), p = 0.003]. Conclusion: The study showed that, against the background of additional administration of hydroxychloroquine in patients with APS with low-level SLE, a decrease in the level of antibodies to cardiolipin ( IgM/IgG ) by 30.4% (p = 0.001) was observed after 3 months of therapy, to β2-glycoprotein I ( IgM/IgG ) - by 28.5% (p = 0.003) after 6 months of therapy. Disclosure of Interests: None declared